The packet wavelet transform in the analysis of phonocardiogram's signals (aortic stenosis and mitral stenosis). (2018) - Meziani, F.; Debbal, S.M.
Heart murmurs are the first signs of cardiac valve disorders. Indeed, heart auscultation through a stethoscope has been recognised for a long time as an important tool for the diagnosis of heart disease. But, it remains insufficient for an efficient treatment of cardiovascular pathologies. The efficiency and accuracy of diagnosis can be improved considerably by using digital signal processing techniques to analyse the phonocardiographic (PCG) signals. The wavelet packet transforms (WPT) was successfully used as a feature to distinguish different heart sounds. It is introduced to analyse and identify the phonocardiogram's signals. The importance of application of the wavelet packet transform (WPT) to analyse the pathological severity of the aortic stenosis 'AS' and mitral stenosis 'MS' was presented. Then, the calculation of various parameters was performed for each patient.